The Inside Story of Taiwan's Quiet Revolution : From Authoritarianism to Open Democracy - Soong, James Chu-yul (Book collections on Project MUSE., 2022)
"By James Soong, a key government and party official, this memoir of the years 1988 to 1993 details Taiwan's successful transition from authoritarianism to democracy. This period saw a nonviolent process commonly referred to as Taiwan's quiet revolution that serves as a case study for political scientists"--